العقد الموقوف - أحمد فنوص حمادي (Journal of Madenat Alelem University College, 2018)
It can be said that the restricted contract is a contract which is immediately affected and its validity is subject to its sanction or revocation. If it becomes valid, it becomes valid retroactively. If the revocation becomes null and void retroactively, and the restricted contract is suspended, if it is held for a reservation or a compulsion or mistake or separation, the restricted contract may be revoked after the demise of reservation or the coercion removal or the error or disclosure of the uniqueness as it allows him to veto if he had to overturn the actions of the eye moved to recover and recovered where he found and traded hands, the eye perished in the hands of the value of the contract and the impugned or arrogant option, The other contract, if he wants, within the forced and guaranteed On the aggrieved and arrogant prostitute that the receipt of the prostitute is hated or arrogant and perished in his hand without any more.